Revisión de Alcance de las Nanopartículas que cruzan la Barrera Hematoencefálica y la Reducción de Tamaño de Tumores Cerebrales en Modelos de Animales: Scoping Review of Nanoparticles that Cross the Blood Brain Barrier and the Reduction of Brain Tumor Size in Animal Models - González De la Cerda, Andrea; Chapa González, Christian (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The present study undertakes a scoping review of research on the size and material of nanoparticles (NPs) that cross the blood brain barrier (BBB) and effectively reduce tumor sizes in animals. Online databases were used to identify papers from which quantitative data could be extracted. The mean size of NPs with proof of BBB penetration and the best performance in brain tumor reduction (or growth inhibition) was of 117 nm. More research should be conducted before stablishing an ideal material for these nanoparticles.